PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT, GREEN ACCOUNTING DAN GREEN STRATEGY TERHADAP KUALITAS LAPORAN KEUANGAN - Wardaningtyas, Dara; Poerwati, Tjahjaning (Jurnal Riset Akuntansi Politala, 2024)
This research’s aim to test and find empirical evidence that strengthnes the research model, analyze and as teaching material about Sustainability Report, Green Accounting and Green Strategy on The Quality of Financial Reports in The Basic Industrial and Chemical Sector manufacturing companies registered with the Indonesian Stock Exchange (BEI) for the 2018 period to 2022. The method used in sampling is Purposive Sampling. The data used is secondary data in the form of company financial reports registered in BEI during 2018 to 2022. The number of samples used in this study was 260 data. The results obtained in this study were Sustainability Report as an effect on the Quality of Financial Reporting, while Green Accounting and Green Strategy did not affect the Quality of Financial Reports.